“General Surgery, Special Surgery, Operative Surgery” – XIX Century Manuscript. The trial of the autorship and publishing date establishing - Tulczyński, Aleksander (Przewodnik Lekarza/Guide for GPs, 2010)
There is an anonymous donator gift, The Central Medical Library has received recently, containing set of three volumes of the surgery, written on handmade paper, without authors name and edition date. First volume, “General Surgery”, contains 189 pages and 3 – alphabetic index of its content: Latin described diseases nomenclature. Second one, “Special Surgery”, contains 303 pages and 14 – alphabetic index as like the previous one. The largest, third volume – 403 pages plus 14 pages of alphabetic index as like the previous ones. Precise studies of the literature has reveald the authors manuscript name. The author is Seweryn Gałęzowski – Vilnious University Professor. He has been working at the University in XIX century (1824-1828).